Virtual Reality in Biology Learning: Systematic Literature Review (SLR) Recent Trends (2003-2023) and Its Post-Pandemic Implications - Maryanti, Sri; Sopandi, Wahyu; Riandi, Riandi (Vidya Karya, 2024)
This study aims to thoroughly describe virtual reality in the biology learning sector in general, the use of VR has been in the spotlight in the last two decades. This study conducted an in-depth bibliometric analysis using the Systematic Literature Review (SLR) method to identify research trends, most frequently researched topics and major contributions in this field based on 24 collected articles indexed by scopus between 2003-2023. We conducted bibliometric analysis using RStudio and VOSviewer. There was the highest increase for virtual reality research in 2021, which is the experience of the corona pandemic in various sectors. The largest average citation was in 2014. Based on the results of the analysis using RStudio and VOSviewer, the keywords virtual reality and biology have been widely carried out and are interrelated with computer programs, but for general biology learning it is still rare so that it can be used as a recommendation for further research gaps. By considering the findings from the bibliometric analysis, this study can provide practical recommendations, summaries and opportunities to find further research gaps. This literature review also underlines how VR research in biology has filled existing knowledge gaps and provided new insights into learning complex biological concepts. Recent studies, especially post-pandemic, have increasingly emphasized the pedagogical effectiveness of VR in improving student engagement, concept understanding, and learning outcomes.